Timing and origins of Mexican and Central American oak diversity - Kieran N. Althaus; Marlene Hahn; Silvia Alvarez-Clare; Jeannine Cavender-Bares; Allen J. Coombes; María del Socorro González-Elizondo; Antonio González-Rodríguez; Paul S. Manos; Hernando Rodríguez-Correa; Susana Valencia-Ávalos; Andrew L. Hipp (Proceedings of the National Academy of Sciences, 2026)
The origins and assembly of temperate biodiversity hotspots remain poorly understood. This knowledge gap is particularly evident in low-latitude montane regions of the Americas, where northern lineages have repeatedly colonized and diversified. Here we investigate the evolutionary history of oaks ( Quercus ) in the Americas, with a focus on their parallel radiation into Mexican and Central American montane forests. Using a time-calibrated phylogeny, we show that white oaks ( Q. section Quercus ) and red oaks ( Q. sect. Lobatae ) independently colonized Mexico c. 25 Mya. This coincides with a variety of ecosystem changes at the Oligocene–Miocene boundary, including aridification. Diversification analyses reveal that montane habitats acted as cradles of oak diversity, with higher speciation rates associated with movement into topographically complex, higher-elevation landscapes. Despite 20 Ma of independent evolution in Mexico and Central America, red and white oaks show remarkable convergent evolution in climate niche. Our results highlight how extrinsic factors—migration into novel environments—coupled with intrinsic niche lability can facilitate rapid diversification. Our study thus provides insights into the origins of temperate biodiversity and the evolutionary processes shaping species-rich montane ecosystems.